Música "Roda Viva": desvendando simbolismos - Raquel Rosan Christino Gitahy; Artemisa Piai Silva de Fernandez; Claudia Karina Ladeia Batista; Alessandro Martins Prado (Universidade Federal de Rondônia, 2019)
The purpose of this paper is to analyze the song "Roda Viva", considering the historical moment of the Brazilian military dictatorship in 1967 lived by the author, Francisco Buarque de Holanda, using the semiotic bias of the conceptual theory of Charles Sanders Peirce. The central focus of this analysis lies in the symbolisms and metaphors used by the author in order to circumvent the political and dictatorial context of that time, making a parallel between the semiotic meanings in the song mentioned. From the analysis carried out, the analytical vision of an entire generation is perpetuated in the face of the authoritarian regime of the dictatorial era.